The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.healun.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

REVEAL risk scores applied to riociguat-treated patients in PATENT-2: Impact of changes in risk score on survival

Abstract: RRS at baseline and Week 12, and change in RRS, were significant predictors of both survival and clinical worsening-free survival. These data support the long-term predictive value of the RRS in a controlled study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 21 publications
(34 reference statements)
4
53
0
Order By: Relevance
“…17,18 Although the post hoc nature of this study could be considered a potential limitation, it is important to note it is unusual (outside of the clinical trial setting) for patients to undergo the extensive battery of tests required to predict risk at every clinic visit, and therefore the RRS was designed to predict risk based on the most recent data available. 19 The RRS has been validated by post hoc calculation in the French Pulmonary Hypertension Network registry cohort, 26 and also in the PATENT 27 and SERAPHIN 28 clinical studies in patients with PAH. Additional limitations include the lack of validation of the RRS in CTEPH, and the high proportion of low-risk patients at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Although the post hoc nature of this study could be considered a potential limitation, it is important to note it is unusual (outside of the clinical trial setting) for patients to undergo the extensive battery of tests required to predict risk at every clinic visit, and therefore the RRS was designed to predict risk based on the most recent data available. 19 The RRS has been validated by post hoc calculation in the French Pulmonary Hypertension Network registry cohort, 26 and also in the PATENT 27 and SERAPHIN 28 clinical studies in patients with PAH. Additional limitations include the lack of validation of the RRS in CTEPH, and the high proportion of low-risk patients at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In post hoc analyses, interventions in clinical trials have been shown to correlate with improvements in the REVEAL risk score. 17 Validation of risk assessment strategies as a surrogate end point should be explored in future clinical trials. 6…”
Section: Discussionmentioning
confidence: 99%
“…7,14 The REVEAL risk calculator predicts survival in diverse PAH populations and provides useful serial survival assessments. 7,10,[13][14][15][16][17][18][19][20] More recently, investigators have derived three additional risk assessment strategies using incident patient populations from the Swedish Pulmonary Arterial Hypertension Register (SPAHR), 21 the Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension (COMPERA), 22 and the French Pulmonary Hypertension Registry (FPHR). 23 These risk assessment strategies are made on the basis of thresholds defined by the European Society of Cardiology and European Respiratory Society (ESC/ ERS) 4 in four to eight variables, and are calculated by various methods.…”
mentioning
confidence: 99%
“…4 Preliminary work suggests it could be useful as an endpoint in clinical trials. 7 An important lesson and recurring theme from multiple prognostication studies is that many patients are not treated aggressively despite intermediate or high-risk features, and despite the evolving data to indicate that more aggressive up-front or early combination therapy and more aggressive use of parenteral prostanoids in higher-risk patients is associated with improved outcomes. In this light, a few high-level recommendations should be considered when deciding on initial treatment options.…”
Section: Step 5: Create An Initial Treatment Strategymentioning
confidence: 99%